Long Noncoding RNA LINC01410 Suppresses Tumorigenesis and Enhances Radiosensitivity in Neuroblastoma Cells Through Regulating miR-545-3p/HK2 Axis - Mou L (OncoTargets and Therapy, 2021)
Liping Mou,1 Lili Wang,2 Shaoming Zhang,3 Qinghua Wang4 1Department of Child Healthcare, People’s Hospital of Rizhao, Rizhao, 276800, Shandong, People’s Republic of China; 2Department of Pediatrics, People’s Hospital of Rizhao, Rizhao, 276800, Shandong, People’s Republic of China; 3Department of Neonatology, People’s Hospital of Rizhao, Rizhao, 276800, Shandong, People’s Republic of China; 4Department of Laboratory, People’s Hospital of Rizhao, Rizhao, 276800, Shandong, People’s Republic of ChinaCorrespondence: Qinghua WangDepartment of Laboratory, People’s Hospital of Rizhao, No. 126, Tai’an Road, Rizhao, 276800, Shandong, People’s Republic of ChinaTel +86-633-3365100Email lwnl5ya@163.comBackground: Abnormal expression of long noncoding RNAs (lncRNAs) was often involved in tumorigenesis and radiosensitivity of various cancers. The aim of this study was to explore the biological function and regulatory mechanism of lncRNA long intergenic non-protein coding RNA 1410 (LINC01410) in tumorigenesis and radiosensitivity of neuroblastoma (NB).Methods: The expression of LINC01410, microRNA-329-3p (miR-545-3p) and hexokinase 2 (HK2) was detected by quantitative real-time polymerase chain reaction (qRT-PCR). Methylthiazolyldiphenyl tetrazolium bromide (MTT) assay, colony formation assay and transwell assay were utilized to detect cell viability, colony formation and cell invasion abilities. Glucose consumption or lactate production was measured by glucose assay kit or lactate assay kit, respectively. The interaction between miR-545-3p and LINC01410 or HK2 was predicted by starBase v2.0 and verified by dual-luciferase reporter, RNA Immunoprecipitation (RIP) and RNA pull-down assays. Western blot was used to measure the protein expression of HK2. The mice xenograft model was established to investigate the role of LINC01410 in vivo.Results: LINC01410 and HK2 were highly expressed while miR-545-3p was lowly expressed in NB tissues and cells. LINC01410 knockdown inhibited tumorigenesis by repressing cell proliferation and invasion, and increased the radiosensitivity via inhibiting colony formation rates and glycolysis. LINC01410 knockdown also suppressed tumor growth in vivo. Moreover, miR-545-3p could bind to LINC01410 and its downregulation reversed the effects of LINC01410 knockdown on tumorigenesis and radiosensitivity. Additionally, HK2 was a direct target of miR-545-3p and its overexpression attenuated the effects of miR-545-3p restoration on suppression of tumorigenesis and promotion of radiosensitivity. Besides, LINC01410 functioned as a molecular sponge of miR-545-3p to regulate HK2 expression.Conclusion: LINC01410 interference inhibited tumorigenesis and increased radiosensitivity via regulating miR-545-3p/HK2 axis, providing a novel therapeutic strategy for NB.Keywords: NB, LINC01410, miR-545-3p, HK2, tumorigenesis, radiosensitivity